A ideia de descentramento em Roberto Schwarz - Costa, Igor Nunes (2012)
This idea of decentering in Roberto Schwarz, arising from subordinated insertion of Brazil in the international parallel to accommodation ideas of modernity by European relations favor of Brazilian society. It is analyzed in the works in which he discusses the development of the country, class relations and intellectual tradition in which it operates. This decentering is emphasized during the Independence of Brazil, made conservatively, when European ideas were put into gravitation elites in Brazilian slave society and patronizing. Such ideas have become ornaments, since the participation of elites in the benefits of advanced societies only be wrought under the economic exploitation and political domination update installed in that period and with the advance of capital. Ideas, so that did not have the same effect it had on countries of origin, always being displaced by favor. Given the relative autonomy of culture facing the economy, the process of formation of Brazil, law, architecture, literature, customs were brought into the country and implemented, contributing to the mismatch between domestic and foreign culture, which is ours under these conditions maladjusted. One of these ideas, the development, founded on science and technology, advancing by leaps stimulated economic structure without due process monitoring social to tell him about it. In fact, according to the regression of this process, since the technological advancement of the core countries could not be accompanied by peripherals, as this keeps advancing, with those countries, ownership of the new product, more productive, making it impossible for the peripheral countries follow the levels of competition, productivity and effectiveness of core. Advancing therefore no related investments in social areas that sustain this progress, exclusion, social segregation, inequality and relations of favor with your choice of components, hierarchy, violence replenished constantly.